2007
DOI: 10.1007/s11695-007-9073-7
|View full text |Cite
|
Sign up to set email alerts
|

Paid Work Increases and State Benefit Claims Decrease after Bariatric Surgery

Abstract: More patients perform paid work after LRYGBP and LAGB than beforehand, and the number of weekly hours they work increases. After surgery, patients claim fewer state benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 27 publications
1
45
1
2
Order By: Relevance
“…13,14 In addition, psychological disorders associated with obesity improve, alongside both quality of life and economic productivity. 4,15,16 Particularly impressive is the rapid and complete resolution of type 2 diabetes in B80% of patients who undergo RYGB. Interestingly, this resolution seems to be independent of weight loss, and occurs within days of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition, psychological disorders associated with obesity improve, alongside both quality of life and economic productivity. 4,15,16 Particularly impressive is the rapid and complete resolution of type 2 diabetes in B80% of patients who undergo RYGB. Interestingly, this resolution seems to be independent of weight loss, and occurs within days of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…8 h per week afterwards. The total time worked per week rose from 1023 to 1611 h, a 57% increase (2) . The study also examined self-reported benefit claims (Disability Living Allowance, Incapacity Benefit and Carer's Allowance).…”
Section: Effect On Paid Workmentioning
confidence: 97%
“…In a study in southwest England, fifty-nine patients were assessed a mean 14 months after surgery (2) . The proportion in paid work after surgery rose from 58% to 76%, which was the same as the population average.…”
Section: Effect On Paid Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrimination individuals with obesity experience is also significant, in terms of accessing employment. 9 Hawkins et al 10 showed…”
Section: Introductionmentioning
confidence: 99%